HEMICHOREA IN A NEWLY DIAGNOSED TYPE 2 DIABETIC PATIENT - Baharum, Nur Haziqah; Zainordin, Nur Aisyah; Warman, Nur’Aini Eddy; Awang, Mohd Hazriq; Mohamad, Aimi Fadilah; Shah, Fatimah Zaherah Mohamed; Ghani, Rohana Abd (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Chorea is a rare neurologic complication of uncontrolled Type 2 Diabetes Mellitus (T2DM). We report the case of an elderly female with newly diagnosed T2DM, presenting with hyperglycaemia-induced right unilateral hemichorea. CASE A 78-year-old female with hypertension and dyslipidaemia presented with one month history of right upper and lower limb involuntary choreiform movements which decreased during sleep. There was no history of fever, neck stiffness, limb weakness, seizure, head trauma, thyrotoxicosis, or a family history of movement disorder. There was no history of intake of medications that can cause chorea. Upon neurological assessment, there was unilateral right hemichorea involving the upper and lower limbs. The examination of higher mental function, cranial nerve, motor, and sensory system were normal. Her plasma glucose on presentation was 22 mmol/L with no evidence of diabetic ketoacidosis or hyperglycaemic hyperosmolar state. Her glycated haemoglobin (HbA1c) was 15.9%. A non-contrast computed tomography of her brain showed a contralateral hyperdensity at the left caudate nucleus. The patient was treated with intravenous insulin and mild improvement in the choreiform movement was seen after initiation of treatment. CONCLUSION Hemichorea is a rare complication of hyperglycaemiainduced involuntary movements. High suspicion of chorea-hyperglycaemia-basal ganglia syndrome should prompt early diagnosis and treatment for diabetes mellitus as delay in recognition and treatment can lead to persistent symptoms and prolonged disability.